2023
DOI: 10.1155/2023/7150917
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Effects of Bacillus subtilis on Growth Performance and Intestinal Microecological Balance of Growing-to-Finishing Pigs

Abstract: The present study investigated the growth performance, immune status, gut morphology, and gut microflora modulation in growing-to-finishing pigs (n = 72; 24 pigs/group) after dietary supplementation with Bacillus subtilis (B. subtilis; two groups (experiment 1 (E1) and experiment 2 (E2): 63 and 98 days, respectively) and control (Ct, basal diet). The results revealed that both 1–98 d and 1–63 d groups significantly improved growth performance, including an increase in midtest body weight (MBW) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Therefore, an immune change can shift the energy utilized in excessive immune stimulation toward growth and improve feed efficiency. Furthermore, our results are well supported by those of a previous study in which growing-to-finishing pigs that received supplementation with B. subtilis had a positive impact on the evident increase in the effect of the probiotic on IgG [43]. However, there were no differences in serum IgA and immunoglobulin M levels between the groups.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, an immune change can shift the energy utilized in excessive immune stimulation toward growth and improve feed efficiency. Furthermore, our results are well supported by those of a previous study in which growing-to-finishing pigs that received supplementation with B. subtilis had a positive impact on the evident increase in the effect of the probiotic on IgG [43]. However, there were no differences in serum IgA and immunoglobulin M levels between the groups.…”
Section: Discussionsupporting
confidence: 91%
“…For the alpha diversity, the continuous treatments lowered richness more than the daily dose condition even after the product was removed from the bioreactor ( Table 4 ). The Bacillus -based product used in our study seemed to be more potent in the diminution of the alpha diversity compared to other studies, especially for the continuous mode of administration [ 40 , 41 ]. This finding could be explained by the duration of the experiment, which was short, the compounds present in the Bacillus -based product, which could bear a strong antimicrobial activity, or the possible synergy between the probiotic secreted antimicrobial compounds or enzymes that increased the microbiota modulation.…”
Section: Discussionmentioning
confidence: 56%
“…After 24 h of treatment, the continuous treatment samples differentiated more from the control when compared to the daily dose treatment, and this remained true over time ( Figure 2 ). Some studies showed no significant change in beta diversity in the gut microbiota when administrating a Bacillus -based probiotic to swine [ 41 , 43 ], but others did [ 40 , 44 ]. This might be due to the length that the treatments were administered, the mode of administration, or a difference in the product tested.…”
Section: Discussionmentioning
confidence: 99%